1980
DOI: 10.1093/jn/110.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Cholesterol on Mitochondrial Function in the Rat

Abstract: Rat-liver mitochondrial cholesterol ester levels were increased nine-fold and free cholesterol levels were doubled by feeding 10% lard and 2% cholesterol with Purina rabbit chow pellets to weanling male Sprague-Dawley rats for 5 weeks. This resulted in depression of State 3 (ADP-stimulated) glutamate respiration and reduced sensitivity to inhibition of phosphyorylation by tetrabutylammonium bromide and oligomycin. Brain, heart, lung, spleen, kidney and testis mitochondrial functions were not responsive to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Excess dietary cholesterol results in hepatomegaly and steatosis, reduced liver complete and total FAO, and decreased ADP‐coupled mitochondrial respiration in rats (Rogers et al . ; Fungwe et al . ), while chemical inhibition of endogenous cholesterol synthesis increased hepatic mitochondrial and peroxisomal FAO with protection from NASH development (Roglans et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Excess dietary cholesterol results in hepatomegaly and steatosis, reduced liver complete and total FAO, and decreased ADP‐coupled mitochondrial respiration in rats (Rogers et al . ; Fungwe et al . ), while chemical inhibition of endogenous cholesterol synthesis increased hepatic mitochondrial and peroxisomal FAO with protection from NASH development (Roglans et al .…”
Section: Discussionmentioning
confidence: 95%
“…The roles of both maladaptive liver cholesterol metabolism and hepatic mitochondrial function have been widely investigated in the development of NAFLD (Min et al 2012;Arguello et al 2015;Bashiri et al 2016). Excess dietary cholesterol results in hepatomegaly and steatosis, reduced liver complete and total FAO, and decreased ADP-coupled mitochondrial respiration in rats (Rogers et al 1980;Fungwe et al 1993), while chemical inhibition of endogenous cholesterol synthesis increased hepatic mitochondrial and peroxisomal FAO with protection from NASH development (Roglans et al 2002;Park et al 2016). In the current study, WD reduced FAO (complete and incomplete) and MRC in both strains, but the LCR rats started at a lower level and remained lower than HCR rats.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most striking observations of our study was the protection from metabolic impairments that was conferred by the genetic deletion of Cyp8b1 Ϫ/Ϫ . Indeed, excessive levels of free cholesterol accumulate in hepatocyte mitochondrial membranes leading to a reduced mitochondrial respiratory output in the livers of NASH patients (22,34).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, direct measurements in NASH patients revealed a 40% reduction in hepatic mitochondrial respiration and a higher incidence of insulin resistance (19). Previous studies have shown that dietary cholesterol induces JNK1-mediated mitochondrial injury, leading to a suppression of State 3 respiration in steatohepatitis (10,22,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation